2008
DOI: 10.3390/ijerph2008050017
|View full text |Cite
|
Sign up to set email alerts
|

Second Hand Smoke Exposure and Excess Heart Disease and Lung Cancer Mortality among Hospital Staff in Crete, Greece: A Case Study

Abstract: Exposure to secondhand smoke (SHS) is a serious threat to public health, and a significant cause of lung cancer and heart disease among non-smokers. Even though Greek hospitals have been declared smoke free since 2002, smoking is still evident. Keeping the above into account, the aim of this study was to quantify the levels of exposure to environmental tobacco smoke and to estimate the attributed lifetime excess heart disease and lung cancer deaths per 1000 of the hospital staff, in a large Greek public hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Research among UK hospitals also revealed that smoking is often noticed despite relevant regulation and policy enforcement is often inadequate [ 5 ] while other studies have also revealed the personnel's similar preference to partial smoking bans and the reluctance of personnel to challenge personnel, visitors and patients to stop smoking on the hospital site [ 6 - 8 ]. Although designated smoking areas of a partial ban might reduce non-smokers exposure to SHS, since smokers might be motivated/encouraged to use the smoking rooms, there is an imminent danger of regression towards ignoring even this partial measure and dramatically increase the already elevated levels of measured SHS exposure within Greek hospitals [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research among UK hospitals also revealed that smoking is often noticed despite relevant regulation and policy enforcement is often inadequate [ 5 ] while other studies have also revealed the personnel's similar preference to partial smoking bans and the reluctance of personnel to challenge personnel, visitors and patients to stop smoking on the hospital site [ 6 - 8 ]. Although designated smoking areas of a partial ban might reduce non-smokers exposure to SHS, since smokers might be motivated/encouraged to use the smoking rooms, there is an imminent danger of regression towards ignoring even this partial measure and dramatically increase the already elevated levels of measured SHS exposure within Greek hospitals [ 9 ].…”
Section: Discussionmentioning
confidence: 99%